Effects of digital game-based learning on achievement, flow and overall cognitive load - Chang, Chi-Cheng; Warden, Clyde A; Liang, Chaoyun; Lin, Guan-You (Australasian Journal of Educational Technology, 2018)
The purpose of this study was to examine differences in learning achievement, flow, and overall cognitive load between digital game-based learning (DGBL) and traditional computer-based learning (CBL). This study was conducted with 103 Taiwan college students: 50 college students in the experimental group used DGBL; 53 students in the control group used CBL. Results show the DGBL participants displayed significantly better learning achievement, flow, and lower cognitive load compared to the CBL participants. Learning achievement and flow exhibit a positive correlation, while negatively correlating with overall cognitive load. These results align with the existing research concepts of flow theory, cognitive theory of multimedia learning, and cognitive load theory.